The Use of Taboo Game in Learning English to Improve Students Vocabulary Mastery - Dianing, Putri; Korompot, Chairil Anwar; Talib, Ahmad (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2025)
This research aims to determine the use of Taboo Game in learning English to improve students vocabulary mastery. This research used a quantitative approach and pre-experimental methods. The sample in this research was 28 students of class VIII-G SMPN 21 Makassar and was selected by using non-probability sampling method, namely purposive sampling by selecting samples based on their own assessment of who is most informative or relevant to the research objectives. Data was obtainde from questionnaire, pre-test and post-test from 28 respondents.The results of the research concluded that: (1) by using Taboo Game strategies, the students vocabulary mastery was considered has a significant results with data analysis obtained from questionnaires, pre-test and post-test which resulted in a very significant increase with a score of 27,2 in the experimental class with 4 indicators, namely spelling, meaning, pronounciation and use. (2) Using taboo games can attract positive perceptions from students and agreeing that the use of taboo games in increasing vocabulary mastery is effective in learning English. (3) The students were interested in learning English by using the Taboo game with the results of 28 respondents as a sample and then recapitulated and analyzed with a total score classification with significant results. So, with the existence of learning innovations with taboo games, it can increase students' learning ability and interest in learning, although the existing indicators need to be improved one by one.Keywords: Taboo Game, Vocabulary Mastery, Learning Interest